Determinants of Capital Structure of Agricultural Firms in Kenya - John Brian Kinyua; Peter W Muriu (European Scientific Journal, ESJ, 2017)
This paper contributes to the capital structure literature by investigating the determinants of capital structure of agricultural firms in Kenya, using annual data for the period 2010-2015. An empirical model to analyze the determinants was specified and estimated using both fixed and random effects estimation techniques. The estimation results provide evidence that profitability, liquidity, age and size of the firm are significant determinants of capital structure. Specifically, the results reveal a negative relationship between profitability and long term debt and a positive relationship between age of the firm and long term debt. We also established a positive influence of age on short term debt, while a negative link is evident between liquidity, the size of the firm and short term debt. The evidence adduced is important for forming credit markets policies for agricultural firms both at the macro and the micro level.